2014
DOI: 10.1155/2014/719837
|View full text |Cite
|
Sign up to set email alerts
|

Change in Anthropometric Parameters of the Posture of Students of Physiotherapy after Three Years of Professional Training

Abstract: Introduction and Aim. A physiotherapist's occupation requires high physical fitness and a properly functioning neuromuscular system. Working with patients is not always performed in accordance with the rules of work ergonomics. The aim of this paper was to verify the possible changes in the posture of students of physiotherapy after three years of professional training. Material and Methods. The sample group consisted of 30 randomly chosen students of physiotherapy. Each person was examined twice (at the age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
(10 reference statements)
1
17
0
Order By: Relevance
“…An important argument is the compatibility of results obtained during photogrammetric assessment and X-ray examination, which currently is recognized as the most accurate method of posture evaluation. Inclinometric and photogrammetric assessments of anteroposterior spinal curvatures are based on the same assumptions as the commonly used Cobb method, which essentially involves identification of angle of inclination in the examined areas with respect to vertical axis [5]. The present study did not find significant differences in the inclination of the specific spinal segments, i.e.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…An important argument is the compatibility of results obtained during photogrammetric assessment and X-ray examination, which currently is recognized as the most accurate method of posture evaluation. Inclinometric and photogrammetric assessments of anteroposterior spinal curvatures are based on the same assumptions as the commonly used Cobb method, which essentially involves identification of angle of inclination in the examined areas with respect to vertical axis [5]. The present study did not find significant differences in the inclination of the specific spinal segments, i.e.…”
Section: Discussionsupporting
confidence: 45%
“…Numerous authors have shown high reliability and usefulness of this method for clinical examinations, e.g. Czaprowski [16], Saur et al [25], Kużdżał et al [5] and Walicka-Cupryś et al [23]. The other device used in the present study for assessing body posture is a system whose operation is based on photogrammetric method taking advantage of Moiré phenomenon.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The achieved result was the average of the measurements. The result of the study was saved in the computer program with the final report from the numerical data and graphs of the scanned points [13, 14]. …”
Section: Methodsmentioning
confidence: 99%